Computational Fluid Dynamics 2008 - Choi, Haecheon; Choi, H. G.; Yoo, J. Y. (Springer Berlin Heidelberg : Imprint: Springer, 2009)
This volume presents the proceedings of the ICCFD 5 - The Fifth International Conference on Computational Fluid Dynamics, held July 07 - 11, 2008 in Seoul, South Korea. The contributions were chosen out of three categories of research: Innovative modeling of flow physics, Innovative algorithm development for flow simulation, optimization and control, and Advanced multidisciplinary applications using the abovementioned innovative technologies.